Analyses of 32 loci clarify phylogenetic relationships among Trypanosoma cruzi lineages and support a single hybridization prior to human contact. - Carlos A Flores-López; Carlos A Machado (Public Library of Science (PLoS), 2011)
The genetic diversity of Trypanosoma cruzi, the etiological agent of Chagas disease, has been traditionally divided in two major groups, T. cruzi I and II, corresponding to discrete typing units TcI and TcII-VI under a recently proposed nomenclature. The two major groups of T. cruzi seem to differ in important biological characteristics, and are thus thought to represent a natural division relevant for epidemiological studies and development of prophylaxis. To understand the potential connection between the different manifestations of Chagas disease and variability of T. cruzi strains, it is essential to have a correct reconstruction of the evolutionary history of T. cruzi.Nucleotide sequences from 32 unlinked loci (>26 Kilobases of aligned sequence) were used to reconstruct the evolutionary history of strains representing the known genetic variability of T. cruzi. Thorough phylogenetic analyses show that the original classification of T. cruzi in two major lineages does not reflect its evolutionary history and that there is only strong evidence for one major and recent hybridization event in the history of this species. Furthermore, estimates of divergence times using Bayesian methods show that current extant lineages of T. cruzi diverged very recently, within the last 3 million years, and that the major hybridization event leading to hybrid lineages TcV and TcVI occurred less than 1 million years ago, well before the contact of T. cruzi with humans in South America.The described phylogenetic relationships among the six major genetic subdivisions of T. cruzi should serve as guidelines for targeted epidemiological and prophylaxis studies. We suggest that it is important to reconsider conclusions from previous studies that have attempted to uncover important biological differences between the two originally defined major lineages of T. cruzi especially if those conclusions were obtained from single or few strains.